2014
DOI: 10.1111/hepr.12415
|View full text |Cite
|
Sign up to set email alerts
|

Update on implications and mechanisms of angiogenesis in liver fibrosis

Abstract: Liver fibrosis occurs as a compensatory response to the process of tissue repair in a wide range of chronic liver injures. It is characterized by excessive deposition of extracellular matrix in liver tissues. As the pathogenesis progresses without effective management, it will lead to formation of liver fiber nodules and disruption of normal liver structure and function, finally culminating in cirrhosis and hepatocellular carcinoma. A new discovery shows that liver angiogenesis is strictly associated with, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(19 citation statements)
references
References 132 publications
(338 reference statements)
0
19
0
Order By: Relevance
“…The incidence of chronic liver diseases such as fibrosis or hepatitis increases with age, and how these affect the efficacy of RIPC is largely unknown. For example, the increased angiogenic activity ongoing with liver fibrosis may interfere with Vegf-dependent protection induced by RIPC 36 ; liver tumors, prime indications for surgery, on their own can produce significant amounts of Vegf and could mask beneficial RIPC effects. Indeed, direct Vegf injection may be used instead of RIPC, as we demonstrated for young mice.…”
mentioning
confidence: 99%
“…The incidence of chronic liver diseases such as fibrosis or hepatitis increases with age, and how these affect the efficacy of RIPC is largely unknown. For example, the increased angiogenic activity ongoing with liver fibrosis may interfere with Vegf-dependent protection induced by RIPC 36 ; liver tumors, prime indications for surgery, on their own can produce significant amounts of Vegf and could mask beneficial RIPC effects. Indeed, direct Vegf injection may be used instead of RIPC, as we demonstrated for young mice.…”
mentioning
confidence: 99%
“…Simultaneously, DNA synthesis and division of ECs occur due to the actions of mitogenic agents, and ECs and pericytes synthesize basement membrane and form lumina. 18) Pericytes penetrate into the segmental centers of lumina and compose the structures of new capillaries. Finally, blood vessel maturation and stabilization occur and ECs secrete growth factors such as PDGF, which attract supporting cells to stabilize the new vessel.…”
Section: Initiation and Regulation Of Angiogene-sismentioning
confidence: 99%
“…When portal venous resistance increases beyond normal compensatory ability, oxygen delivery is reduced. 18) Hypoxia acts as an aggravating factor of cell damage and inflammation as well as a most potent stimulant for angiogenesis, with the transcription of hypoxia-sensitive pro-angiogenic genes modulated through HIFs. Hypoxia is a major factor implicated in the induction of VEGF through a pathway that involves the transcription factor HIF-1α.…”
Section: Angiogenesis In Liver Fibrosismentioning
confidence: 99%
“…The Notch pathway is also an important mediator in angiogenesis that enhances blood vessel stability and increases the aorta inner diameter by reducing the response of endothelial cells (ECs) to vascular growth factors. Recent reports indicated that VEGF can induce HSCs to express Notch ligands to promote angiogenic responses (Zhang et al 2015). The transfer of Notch3 shRNA carried by recombinant adeno-associated virus type 1 (rAAV1) vector to livers improved liver fibrosis in rats treated with CCl4 by decreasing the expression of TGF-β and increasing the expression of E-cadherin, suggesting that Notch is a promising target for liver fibrosis therapy ).…”
Section: Other Relevant Molecular Targets and Other Possible Anti-fibmentioning
confidence: 99%